ANALISA UJI PERBANDINGAN KEAUSAN KAMPAS REM CAKRAM ANTARA KAMPAS REM MITSUBISHI DENGAN KAMPAS REM INDOPART PADA KENDARAAN MITSUBISHI L 300 - Wijanarko, Heri; Sugihandoko; Lufti, Aryananta (JURNAL MEKANIKASISTA, 2024)
To determine the quality of brake pads, this writing explains the method for assessing the quality of Mitsubishi and Indopart brake pads through three testing processes: Brinell hardness test, wear test, and material composition test. In the Brinell hardness test, data is obtained by creating specimens for each brake pad, and each specimen undergoes testing at 3 different points on the brake pad surface. The wear test follows a similar procedure to the hardness test, but the results are obtained using a wear testing machine. For the material composition test, the dominant elements present in the brake pads are determined using analytical chemical solutions. This allows identification of the dominant elements in both Mitsubishi and Indopart brake pads.